Postoperative residual curization in geriatric patients: a prospective, observational cohort study - Sonmez, Emine; Guven Aytac, Betul; Postaci, Aysun (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the occurrence and potential risk factors of residual curarisation after surgery and the subsequent acute respiratory events in elderly patients. Method: The prospective, cohort study was conducted at Ankara City Hospital from July to December 2021, and comprised data of geriatric patients undergoing elective surgery under general anaesthesia using moderate-acting nondepolarising muscle relaxants. Postoperative acute respiratory events in the post-anaesthesia care unit were subsequently noted. Data was analysed using SPSS 25. Results: Of the 185 patients aged >65 years evaluated, 174(94%) were included; 88(50.6%) females and 86(49.4%) males. The incidence of residual curarisation was in 6(3.4%) patients. Postoperative residual curarisation was significantly associated with smooth recovery process (p<0.05). The recovery was associated with intraoperative bleeding, total dose of neuromuscular blocker, and the length of time from the last dose of neuromuscular blocker to antagonist administration (p<0.05). Postoperative critical respiratory events were more common in patients with postoperative residual curarisation (p< 0.001). The length of stay in post-anaesthesia care unit was 1.57 times longer in such patients (p=0.001). Conclusion: Postoperative residual curarisation increased length of hospital stay and respiratory complications. Key Words: Postoperative residual curarisation, Neuromuscular monitoring, Anaesthesia recovery period, Sugammadex, Postoperative care, Elderly patient.